Ruth Watson: The Really Helpful Cookbook - Davidson, Alan E (Petits Propos Culinaires, 2025)
Ruth Watson: The Really Helpful Cookbook: Ebury Press, 2000: ISBN 0-091-87798-9: 288 pp, colour photographs by William Lingwood, index, hardback, £20.00.